Decision Making Framework Supported By Knowledge Management Activities - Noman, Marwan Hesham; Aziz, Azira Abd (Journal of Knowledge Management Practice, 2011)
Managerial positions have been known as the most eligible positions for decision making. All organizations are entitled to have a decision every day and be responsible of its results. This research is going to help the managers’ managerial thinking by providing a new framework of decision making techniques. The techniques are available through books, articles and journals, but the key is how the organizations combine these methods into one framework and get mixture of decision making methods. There are two focuses of knowledge management enablers in this study, which are culture and infrastructure. Most of decision making failure opportunities are related to people in the first phase which is part from infrastructure, and culture in the second phase since company and country regulations will play an important role toward decision making. The study will be analyzing those behaviors based on the resulted inputs from the collected data. In the findings area, objectively the results should come out to show the comparison strategy between the exciting frameworks in the literature review and the data collected. This study will report the decision strengths and weaknesses derived from questionnaires and interviews. Semantic analysis will take place to compare the results with the existing mechanisms found in the literature review.
Keywords: knowledge management; Decision making models; Cultural factors; Industrial factors; Technology tools; Knowledge sharing; Knowledge factors